Pacific lowland snakes of the genus Atractus (Serpentes: Dipsadidae), with description of three new species - Passos, Paulo; Mueses-Cisneros, Jonh Jairo; Lynch, John D.; Fernandes, Ronaldo (Zootaxa, 2009)
The taxonomic status of the Pacific lowland Atractus is revised on the basis of meristic, morphometric, colour pattern, and hemipenial characters. Geographical variation is reported for six Atractus species (A. boulengerii, A. clarki, A. iridescens, A. melas, A. multicinctus, and A. paucidens). Atractus boulengerii is rediscovered and redescribed from a specimen from the Colombian coast. The first voucher specimens are reported for A. melas. The current status of A. microrhynchus is maintained based on the discovery of new material referrable to that species. Three new species of Atractus are described from the Pacific lowland of Colombia: A. echidna sp. nov., A. medusa sp. nov., A. typhon sp. nov. Two new Atractus species groups (multicinctus and paucidens) are proposed based on external morphology, maxillary dentition, and hemipenial characters. A new key to Pacific lowland species of Atractus is provided.